On the regulation of social norms - Dorothea Kübler (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2000)
A model is developed to understand how norms can be influenced by norm entrepreneurs, e.g. lawmakers, government agencies, unions etc. Two instruments of influencing the dynamics of normfollowing behavior are analyzed, namely transforming the (monetary) incentives and changing the meaning or the reputational value of following a norm. First, incentives can be introduced (e.g. fines or subsidies imposed by government agencies) to violate existing norms or follow a new code of behavior. Second, actors can be convinced by norm entrepreneurs, e.g. using moral suasion, that following the existing norm is inappropriate or that following a certain new norm is appropriate. Both forms of norm regulation are incorporated into Akerlof's model of social custom (1980) in order to derive the comparative static properties of norm destruction and norm creation for different types of norms.
urn:nbn:de:kobv:11-10047479
Keywords: 330; social norms; regulation; conformity